Artificial Intelligence (AI)-Driven Mediated Communication Strategies: A Case Study of Sellers in Shopee's Live Streaming E-Commerce Platform - Siti Retno Wulandari; Ana Noviani; Andhika Prasetyo; Irwansyah Irwansyah (Greenation International Journal of Law and Social Sciences, 2026)
The utilization of live-streaming features on e-commerce platforms such as Shopee creates a real-time interaction space between sellers and consumers. At the same time, artificial intelligence (AI) technologies, including chatbots and automatic recommendation systems, increasingly shape the communication patterns within this space. This study, AI-Driven Mediated Communication Strategies: A Case Study of Sellers in Shopee’s Live Streaming E-Commerce Platform, examines how AI features influence the communication strategies employed by business operators during live streaming. Using an interpretive qualitative approach, this research involved three active Shopee sellers who regularly conduct live-streaming activities. The analysis draws on Actor-Network Theory (ANT) and AI-Mediated Communication (AIMC). The findings show that AI functions as a non-human actor within the communication network between sellers and buyers. AI supports interaction by answering common questions automatically, displaying relevant products, and helping sellers adjust their communication strategies. Thus, AI is no longer merely a supporting tool, but also an active partner in shaping digital communication in e-commerce.